Stabilizing lithium metal anode by octaphenyl polyoxyethylene-lithium complexation - Hongliu Dai (Nature Portfolio, 2020)
Despite the large theoretical promise of Li metal anode, the dendrite growth poses a serious safety challenge. Here the authors address this issue by adding octaphenyl polyoxyethylene as an electrolyte additive which facilitates the formation of a dual-functional layer and excellent performance.